Problem Based Learning: Melatihkan Keterampilan Pemecahan Masalah untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi IPA: Problem Based Learning: Melatihkan Keterampilan Pemecahan Masalah untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi IPA kelas IX - Oktavia, Rela Setyawati; Harir, Ahmad Habib; Rosdiana, Laily (UNIB Press, 2024)
This research aimed to enhance problem-solving abilities and improve student learning outcomes. Problem-based learning (PBL) was employed as the instructional model to develop students' problem-solving skills. The study adopted a classroom action research approach spanning two learning cycles, encompassing stages of planning, implementation, observation, and reflection. The research involved 39 students from class IX E at SMPN 56 Surabaya. Data collection methods include observation, interviews, and written tests. The collected data was processed and analyzed descriptively to illustrate improvements in learning outcomes. The analysis reveals that the implementation of the problem-based learning model resulted in significant enhancements in student learning outcomes across the pre-cycle stage, Cycle I, and Cycle II, categorized as quite good. Notably, there was a 42.07% increase in student learning outcomes from the pre-cycle stage to Cycle I. Moreover, from Cycle I to Cycle II, there was a further increase of 24.37% in student learning outcomes.